Alternativas em microdrenagem para solucionar a interrupção de um ramal coletor de água pluvial - Valentim, Vinicius de Moraes (Universidade Federal de São Carlos, 2021)
Hydrological cycle is one of the main natural phenomena on the planet. this cycle allows the circulation of water over the surface, the subsoil and the earth's atmosphere in its different physical states. The accelerated urban growth process causes interference in this dynamic. Numerous floods occur due to the waterproofing process of the soils, which increases the volume of surface water runoff and reduces the infiltration rate. In this perspective, it is necessary to implement drainage structures of the rainwater along the extension of urban areas. These structures capture the waters from precipitation and direct to streams, rivers and oceans. However, the alteration of any systems already implemented may incur a failure in the efficiency of the system, making it necessary to use engineering instruments to avoid incidence of this problem. The present work aims to carry out a study of quantitative survey about the impact caused by the interruption of a branch in a subdivision of the city of Ourinhos-SP, Brazil. The development of parameters used hydrological aspects of the site, the map of stormwater galleries and the topographical plan of the region, provided by the city's urban development department. From of the data obtained, calculations were performed in accordance with the relevant literature. After this calculation, it was possible to define which compensatory drainage technique (detention basin) most appropriate for the situation. Upon obtaining these resultados data, the system has been dimensioned.
Alternatives in microdrainage for resolve the interruption of a stormwater collector
Keywords: Hidrologia urbana; Sistema de drenagem; Técnicas compensatórias; Hydrology; Urban drainage; Microdrainage system; ENGENHARIAS::ENGENHARIA CIVIL; ENGENHARIAS::ENGENHARIA SANITARIA